Does Punishing Sanctions Busters Work? Sanctions Enforcement and U.S. Trade with Sanctioned States. (September 2022) - Early, Bryan R.; Peterson, Timothy M.
How can the government agencies responsible for enforcing economic sanctions enhance their effectiveness? This study explains how and why sanctions enforcement actions undertaken by sender governments can discourage their firms from trading with the states they sanction. Specifically, we examine how the penalties imposed against sanctions violators by the U.S. Department of Treasury's Office of Foreign Asset Control (OFAC) affect U.S. firms' trade with target states. We argue that because U.S. firms are responsive to the risk of being penalized and the disruptions that penalties create, U.S. trade with sanctioned states will be lower in the aftermath of OFAC enforcement actions. The penalties' frequency and severity will magnify those negative effects. We hypothesize that OFAC enforcement actions taken against both U.S. and foreign sanctions violators will negatively impact U.S. trade with targets. Analyzing data from 2003 to 2015, we find that OFAC's sanctions enforcement actions decrease U.S. trade with sanctioned states in numerous ways.